2020
DOI: 10.25130/j.v25i2.958
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Potentiality and Depositional Environment of Naokelekan Formation in Binari Serwan-1 Well, NE-Iraq Using Infrared Factors and Palynological Analysis Evidence

Abstract: The cuttings from the Jurassic Naokelekan Formation have been studied in the oil exploratory Binari-Serwan-1 Well in Dokan Town, Iraqi Kurdistan Region, NE Iraq. Both infrared spectrometry techniques and microscopic study were used for determining hydrocarbon generation potentiality. The prepared strewn slides have been studied under polarizing microscope. The Naokelekan Formation has revealed an excellent total organic carbon (TOC) wt. % content, ranging from 4.20 to 5.88 wt. %. The palynomorphs as well as ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is supposed that the deep‐water conditions in SIB continued throughout the Jurassic and also extended to the Cretaceous Garau or Balambo intrashelf basin (Aqrawi et al, 2010; Jassim & Goff, 2006). For example, in the Kurdistan region, due to the persistence of the Sargelu and Naokelekan deep‐water deposition (the Najmah Formation equivalent), the basin lasted throughout the Jurassic and Cretaceous (e.g., Abdula, 2017; Abdula, Abdulla, Salih, Isa, & Hashmi, 2020; Alsharhan, 2014; Sharezwri, Nourmohammadi, & Abdula, 2019). However, in NW Iran, evidence of an abrupt shift of the middle Jurassic basinal facies into the upper Jurassic peritidal carbonate platform suggests that HIB (the SIB equivalent) and the Pars intrashelf basin in SW Iran have only persisted until the MLJT.…”
Section: Discussionmentioning
confidence: 99%
“…It is supposed that the deep‐water conditions in SIB continued throughout the Jurassic and also extended to the Cretaceous Garau or Balambo intrashelf basin (Aqrawi et al, 2010; Jassim & Goff, 2006). For example, in the Kurdistan region, due to the persistence of the Sargelu and Naokelekan deep‐water deposition (the Najmah Formation equivalent), the basin lasted throughout the Jurassic and Cretaceous (e.g., Abdula, 2017; Abdula, Abdulla, Salih, Isa, & Hashmi, 2020; Alsharhan, 2014; Sharezwri, Nourmohammadi, & Abdula, 2019). However, in NW Iran, evidence of an abrupt shift of the middle Jurassic basinal facies into the upper Jurassic peritidal carbonate platform suggests that HIB (the SIB equivalent) and the Pars intrashelf basin in SW Iran have only persisted until the MLJT.…”
Section: Discussionmentioning
confidence: 99%
“…Abdula et al [10] through the Rock-Eval analysis and organic petrographical characterization of the upper Jurassic Naokelekan formation, northern Mesopotamian basin, Kurdistan region-Iraq, evaluated the formation and concluded that the Naokelekan Formation contains types II and III kerogen. Abdula et al [11] studied the hydrocarbon potentiality and depositional environment of Naokelekan Formation in Binari Serwan-1 Well, NE-Iraq using infrared factors and palynological analysis evidence. Sharezwri et al [12] concluded through his study on the Naokelekan Formation that this formation was mainly deposited within a ramp setting in two sub-environments: lagoon and shallow marine.…”
Section: Introductionmentioning
confidence: 99%